2018
DOI: 10.1210/en.2018-00083
|View full text |Cite
|
Sign up to set email alerts
|

CC-401 Promotes β-Cell Replication via Pleiotropic Consequences of DYRK1A/B Inhibition

Abstract: Pharmacologic expansion of endogenous β cells is a promising therapeutic strategy for diabetes. To elucidate the molecular pathways that control β-cell growth we screened ∼2400 bioactive compounds for rat β-cell replication-modulating activity. Numerous hit compounds impaired or promoted rat β-cell replication, including CC-401, an advanced clinical candidate previously characterized as a c-Jun N-terminal kinase inhibitor. Surprisingly, CC-401 induced rodent (in vitro and in vivo) and human (in vitro) β-cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 54 publications
5
102
0
2
Order By: Relevance
“…Since de-differentiation of beta cells occurs in both mice and humans with type 2 diabetes (Cinti et al, 2016; Talchai et al, The effects of harmine alone, and of various TGFbSF ligand inhibitors, some of which are specific for TGFb receptors, and others for activin, inhibin, and BMP receptors. As can be seen, and as reported previously (Aamodt et al, 2016;Abdolazimi et al, 2018;Dirice et al, 2016;Shen et al, 2015;Wang et al, 2015aWang et al, , 2016, harmine induces Ki67 labeling in approximately 2% of normal human beta cells, and TGFbSF inhibitors lead to only marginal Ki67 labeling. However, each of the TGFbSF inhibitors in combination with harmine induces striking increases in Ki67 labeling in beta cells.…”
Section: Harmine-tgfbsf Inhibitor Combinations Enhance Markers Of Humsupporting
confidence: 87%
See 3 more Smart Citations
“…Since de-differentiation of beta cells occurs in both mice and humans with type 2 diabetes (Cinti et al, 2016; Talchai et al, The effects of harmine alone, and of various TGFbSF ligand inhibitors, some of which are specific for TGFb receptors, and others for activin, inhibin, and BMP receptors. As can be seen, and as reported previously (Aamodt et al, 2016;Abdolazimi et al, 2018;Dirice et al, 2016;Shen et al, 2015;Wang et al, 2015aWang et al, , 2016, harmine induces Ki67 labeling in approximately 2% of normal human beta cells, and TGFbSF inhibitors lead to only marginal Ki67 labeling. However, each of the TGFbSF inhibitors in combination with harmine induces striking increases in Ki67 labeling in beta cells.…”
Section: Harmine-tgfbsf Inhibitor Combinations Enhance Markers Of Humsupporting
confidence: 87%
“…While DYRK1A inhibitors such as harmine, 5-IT, INDY, and GNF4877 have been shown to induce replication in human beta cells, the ''rates'' of proliferation or labeling indices have been low, in the 1.5%-3% range in vitro (Aamodt et al, 2016;Abdolazimi et al, 2018;Dirice et al, 2016;Shen et al, 2015;Wang et al, 2015aWang et al, , 2016, and far lower in in vivo transplant models Wang et al, 2015a). Thus, while harmine analog-induced beta cell proliferation is an important advance, one might envision higher rates of proliferation as being required for therapeutic human beta cell expansion in type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group found that harmine is able to induce human β-cell proliferation and DYRK1A-NFAT pathway as being the major pathway for this cell proliferation [5]. These results have been confirmed in other labs with other DYRK1A inhibitors unrelated to the harmine scaffold, including from our own lab [6,8,[34][35][36][37]. Since, modification of harmine has not been explored previously in context of β-cell proliferation, we therefore decided to carry out structure-activity relationship studies of harmine for both DYRK1A inhibition and β-cell proliferation.…”
Section: Introductionsupporting
confidence: 61%